Update of Pheochromocytoma Syndromes: Genetics, Biochemical Evaluation, and Imaging - Alrezk, Rami; Suarez, Andres; Tena, Isabel; Pacak, Karel (Frontiers in Endocrinology, 2018)
Pheochromocytomas (PCCs) are tumors of the chromaffin cells that arises within the adrenal medulla, whereas, paragangliomas (PGLs) are neural crest-derived neuroendocrine neoplasms arising from the extrarenal paraganglia. Pheochromocytomas and paragangliomas syndromes (PPGLs) are rapidly evolving field in endocrinology and oncology. Discoveries over the last decade and especially over the last few years has significantly improved our understanding of PPGLs. Recent advances included the findings of newly related syndromes in PPGL and its associated susceptibility genes. Besides, new radiological functional studies and targeted radionuclide therapy have improved the diagnostic accuracy and provided new tools for treatment. In this review article, we will present recent advances in this field and recommend new biochemical classification that better reflect our new understanding of the disease.